Olutasidenib (FT-2102) in patients with relapsed or refractory IDH1-mutant glioma: A multicenter, open-label, phase Ib/II trial. Issue 1 (25th May 2022) - de la Fuente, Macarena I; Colman, Howard; Rosenthal, Mark; Van Tine, Brian A; Levacic, Danijela; Walbert, Tobias; Gan, Hui K; Vieito, Maria; Milhem, Mohammed M; Lipford, Kathryn; Forsyth, Sanjeev; Guichard, Sylvie M; et al.
Abstract: Background: Olutasidenib (FT-2102) is a highly potent, orally bioavailable, brain-penetrant and selective inhibitor of mutant isocitrate dehydrogenase 1 (IDH1). The aim of the study was to determine the safety and clinical activity of olutasidenib in patients with relapsed/refractory gliomas harboring an IDH1 R132X mutation. Methods: This was an open-label, multicenter, nonrandomized, phase Ib/II clinical trial. Eligible patients (≥18 years) had histologically confirmed IDH1 R132X -mutated glioma that relapsed or progressed on or following standard therapy and had measurable disease. Patients received olutasidenib, 150 mg orally twice daily (BID) in continuous 28-day cycles. The primary endpoints were dose-limiting toxicities (DLTs) (cycle 1) and safety in phase I and objective response rate using the Modified Response Assessment in Neuro-Oncology criteria in phase II. Results: Twenty-six patients were enrolled and followed for a median 15.1 months (7.3‒19.4). No DLTs were observed in the single-agent glioma cohort and the pharmacokinetic relationship supported olutasidenib 150 mg BID as the recommended phase II dose. In the response-evaluable population, disease control rate (objective response plus stable disease) was 48%. Two (8%) patients demonstrated a best response of partial response and eight (32%) had stable disease for at least 4 months. Grade 3‒4 adverse events (≥10%) included alanine aminotransferase increased and aspartate aminotransferase increased (three [12%], each). Conclusions: Olutasidenib 150 mg BID was well tolerated in patients with relapsed/refractory gliomas harboring an IDH1 R132X mutation and demonstrated preliminary evidence of clinical activity in this heavily pretreated population.